Diseño de un sistema de mejora de autonomía para un vehículo eléctrico (2020)
This project seeks to increase the autonomy of an electric vehicle, with the design of a system that allows more efficient use of energy, since currently in Colombia electric vehicles are only for exclusive use within the city, With the need to help with the environment, an energy collection system from the air is analyzed, in order to provide a solution to the problem. Taking into account information provided by the EVCO company and a pertinent analysis of the system, the best option in terms of economy is sought in this way, improvement in performance and thus meet the objectives set.